The influence of Good or Negative Attitude Person’s on Performance at Workplace - Adinda Okta Tiara; Ezha Mahendra; Ananda Fortunisa (Proceeding International Conference on Religion, Science and Education, 2023)
Attitude is a very important factor in the workplaces. Because attitude affects work continuity, a good attitude will improve communication efficiency and better collaboration during work. This research was carried out using the literature review method. The articles reviewed were collected using workplace attitudes keywords and 100 articles were produced. After going through the elimination stages, looking at subjective factors resulted in 30 articles. From this research it was found that attitude is a very important factor in the world of work. A good attitude is respect for others, commitment to the job, Helpfulness with Others. Meanwhile, a negative attitude is always complaining, making the same mistake many times and delaying work. Attitude towards work is influenced by internal and external factors. Internal factors are factors that come from within, such as emotional and psychological, intimacy with colleagues, and the comfort of creating yourself. External factors are factors that come from outside or the environment such as workplace atmosphere, rest time, length of work, wages and incentives. Even though attitude is not inborn, one’s attitude and character are very difficult to change, especially if the change you want is a significant change. that’s why with a good attitude will be able to create a new atmosphere in the work environment that is more comfortable. Someone with a positive attitude encourages colleagues to work harder, stay focused and push to achieve their goals. A positive will lead to more positives, while a widespread negative attitude can have a negative impact on performance, causing employees to become apathetic and discouraged. If a customer or client encounters a bad attitude from an employee, they won’t come back.